Tipping points and economic recovery in Macau - Morrison, Keith (Macau Business, 2022)
Macau, Macau Business, MAG, MB, MB Featured, Opinion | New year; old problem. As the pandemic rolls on, so many calls for economic diversification in Macau as a survival strategy have been heard, loud and long, that, as the law of diminishing returns tells us, their effects recede.